Nanometer silicon carbon negative electrode material and preparation method and application thereof

By loading metal oxides and graphene in nano-silicon carbon anode material, the performance of nano-silicon carbon materials in lithium-ion batteries is solved, and the circulation is significantly improved Performance and reduced expansion rate.

CN119133412APending Publication Date: 2024-12-13NINGBO GRAPHENE INNOVATION CENT CO LTD

Patent Information

Application Number
CN202411361260.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Nanosilicon carbon anode material has poor volume changes and poor circulation performance due to high lithium embedded capacity in lithium-ion batteries, especially due to the slurry and shedding of silicon, resulting in high expansion rate and poor circulation performance.

Method used

Using porous carbon material as the substrate, nanosilicon is deposited in its pores, and metal oxides and graphene are loaded on the surface and pores of porous carbon material, through the low expansion rate of metal oxides and high mechanical strength and thermal conductivity of graphene. , optimize material performance, reduce first expansion rate and improve cycle performance.

Benefits of technology

Achieve a lower first expansion rate and a significantly improved 100-turn cycle performance. Compared with the modification of metal oxide or graphene alone, the first expansion rate is reduced by 5% and the cycle performance is improved by 26%; or the first expansion rate is reduced by 3% , cycling performance is improved by 11%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a nanometer silicon-carbon negative electrode material and a preparation method and application thereof. The nanometer silicon-carbon negative electrode material provided by the invention comprises a porous carbon material, nanometer silicon and metal oxide which are loaded in pores of the porous carbon material, and metal oxide and graphene which are loaded on the surface of the porous carbon material. The metal oxide and the graphene are adopted to modify the porous carbon material loaded with the nano silicon, and the metal oxide enters the pore channels of the porous material while the porous carbon material is coated, so that the first expansion rate of the nano silicon-carbon negative electrode material is reduced, and the cycle performance of the nano silicon-carbon negative electrode material is improved. Experimental results show that compared with modification by singly adopting the metal oxide, the first expansion rate is reduced by 5%, and the 100-circle cycle performance is improved by 26%; and compared with single graphene modification, the first expansion rate is reduced by 3%, and the 100-circle cycle performance is improved by 11%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery application technology, and in particular to a nano silicon-carbon negative electrode material, a preparation method thereof and an application thereof. Background Art

[0002] The theoretical lithium insertion capacity of silicon is as high as 4200mAh / g, which is much higher than the theoretical capacity of commercial graphite anodes (the theoretical capacity of graphite anode materials is only 372mAh / g), and is considered to be the first choice for the next generation of lithium-ion battery anode materials. However, the high lithium insertion capacity will inevitably lead to severe volume changes, which makes silicon easy to pulverize and fall off.

[0003] The most simple and effective method for preparing nano silicon-carbon negative electrode materials is to deposit nano silicon in the nano-scale pores of porous carbon materials through chemical vapor deposition. This type of nano silicon-carbon negative electrode material stabilizes the material structure through the nano-scale confined structure in the carbon material, which can inhibit the volume expansion of silicon during the cycle to a certain extent, but its initial expansion rate is still as high as nearly 30%, and the cycle performance is poor. In addition, in the prior art, silicon is deposited on the surface and inside of the porous carbon material. The silicon deposited on the surface of the porous carbon material is easy to agglomerate, and the generated silicon grain size is larger, and the expansion will be more significant, which will further affect the cycle performance of the silicon-carbon negative electrode material. Summary of the invention

[0004] In view of this, the present invention provides a nano silicon-carbon negative electrode material, a preparation method thereof and an application thereof. The nano silicon-carbon negative electrode material provided in the present application has a low initial expansion rate and good cycle performance.

[0005] The present application provides a nano silicon-carbon negative electrode material, comprising:

[0006] Porous carbon materials;

[0007] Nano-silicon and metal oxides loaded in the pores of the porous carbon material;

[0008] Metal oxide and graphene are loaded on the surface of the porous carbon material.

[0009] In some specific implementations, the nano silicon carbon negative electrode material includes:

[0010] 40wt%~55wt% porous carbon material;

[0011] 40wt%~55wt% nano silicon;

[0012] 0.5wt%~5wt% of metal oxide;

[0013] 0.3wt%~5wt% graphene.

[0014] In some specific implementations, the specific surface area of ​​the porous carbon material is 1300 m 2 / g ~2200m 2 / g; micropores account for 40%~90%; average pore size is 1.8nm~4nm; pore volume is 0.6 cc / g ~1.1cc / g.

[0015] In some specific implementations, the metal oxide is selected from at least one of TiO2, Al2O3, ZrO2, SnO2, ZnO, Fe2O3 and Co3O4;

[0016] In some specific implementations, the nano silicon carbon negative electrode material further includes a passivation layer coated on the surface of the nano silicon.

[0017] In some specific implementations, the passivation layer is amorphous carbon or silicon oxide (SiO x ).

[0018] The present application also provides a method for preparing the nano silicon-carbon negative electrode material described in the above technical solution, comprising the following steps:

[0019] a) depositing nano-silicon on a porous carbon material as a substrate, so that the nano-silicon is deposited in the pores of the porous carbon material to obtain a porous carbon material loaded with nano-silicon;

[0020] b) Modifying the porous carbon material loaded with nano-silicon by using metal oxide and graphene, so that the metal oxide is loaded in the pores and on the surface of the porous carbon material, and the graphene is loaded on the surface of the porous carbon material, to obtain a nano-silicon-carbon negative electrode material.

[0021] In some specific implementations, step a) specifically includes:

[0022] Chemical vapor deposition is carried out using a porous carbon material as a substrate and silane as a silicon source, so that the mass ratio of the porous carbon material to the silicon deposition amount is 1:0.67-1.22, thereby obtaining a porous carbon material loaded with nano-silicon.

[0023] In some specific implementations, step b) specifically includes:

[0024] The porous carbon material loaded with nano-silicon is dispersed and mixed with a metal oxide precursor and a graphene dispersion, and then subjected to heat treatment to obtain a nano-silicon-carbon negative electrode material;

[0025] Alternatively, step b) specifically comprises:

[0026] The porous carbon material loaded with nano-silicon is dispersed, mixed with a metal oxide precursor, and heat-treated, and then mixed with a graphene dispersion and heat-treated to obtain a nano-silicon-carbon negative electrode material.

[0027] In some specific implementations, before step b), the following steps are further included:

[0028] Deposition of a passivation layer is performed using a porous carbon material loaded with nano-silicon as a substrate;

[0029] The passivation layer is amorphous carbon or silicon oxide.

[0030] The present application also provides an electrode plate, comprising the nano silicon-carbon negative electrode material described in the above technical solution or the nano silicon-carbon negative electrode material prepared according to the preparation method described in the above technical solution.

[0031] The present application also provides a battery cell, comprising the electrode plate described in the above technical solution.

[0032] The present application provides a nano silicon carbon negative electrode material, including a porous carbon material, nano silicon and metal oxides loaded in the pores of the porous carbon material, and metal oxides and graphene loaded on the surface of the porous carbon material. The present application uses metal oxides and graphene to modify the porous carbon material loaded with nano silicon, making full use of the low expansion rate and high mechanical stability of metal oxides, and the high electrical conductivity, high mechanical strength, and high thermal conductivity of graphene. While coating the porous carbon material, the metal oxide enters the pores of the porous material to reduce the first expansion rate of the nano silicon carbon negative electrode material and improve its cycle performance. The experimental results show that compared with the modification using metal oxide alone, its first expansion rate decreases by 5%, and the 100-cycle cycle performance increases by 26%; compared with the modification using graphene alone, its first expansion rate decreases by 3%, and the 100-cycle cycle performance increases by 11%. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of the preparation method provided in the embodiment of the present application;

[0034] Figure 2 This is a SEM image of the TiO2 / graphene synergistically modified nano-silicon-carbon negative electrode material prepared in Example 1;

[0035] Figure 3 This is the first cycle charge and discharge curve of the TiO2 / graphene synergistically modified nano silicon carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0036] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0037] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0038] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0039] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0040] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0041] The present application provides a nano silicon-carbon negative electrode material, comprising:

[0042] Porous carbon materials;

[0043] Nano-silicon and metal oxides loaded in the pores of the porous carbon material;

[0044] Metal oxide and graphene are loaded on the surface of the porous carbon material.

[0045] The present application uses metal oxides and graphene to modify porous carbon materials loaded with nano-silicon. The metal oxides have low expansion rate, high mechanical stability, and high electron ion transmission characteristics when lithium is inserted and removed. Graphene has high electrical conductivity, high mechanical strength, and high thermal conductivity. It is an excellent carbon coating material. The synergistic modification of the two can optimize the performance of silicon-carbon negative electrode materials, making them have the physical properties of low expansion and high mechanical strength, and improving their cycle performance.

[0046] The nano silicon carbon negative electrode material provided in the present application includes a porous carbon material having a pore structure. In some specific implementations, the specific surface area of ​​the porous carbon is 1300 m 2 / g ~2200m 2 / g, preferably 1500m2 / g ~2000m 2 / g; the proportion of micropores is 40%~90%, preferably 50%~80%, and more preferably 60%~70%; the average pore size is 1.8nm~4nm, preferably 2nm~3.5nm, and more preferably 2.5nm~3nm; the pore volume is 0.6 cc / g ~1.1cc / g, and preferably 0.8cc / g ~1 cc / g. The present application has no special restrictions on the precursor for preparing the porous carbon material, which can be at least one of biomass, asphalt, petroleum coke, resin and its derivatives, that is, the porous carbon material can be a biomass-based porous carbon material, an asphalt-based porous carbon material, a petroleum coke-based porous carbon material, a resin and its derivative-based porous carbon material. The present application has no special restrictions on the source of the porous carbon material, which can be prepared according to methods familiar to those skilled in the art, or purchased on the market.

[0047] The porous carbon material is loaded with nano silicon and metal oxide in the pores, wherein the nano silicon can be formed in the porous carbon material pores in a deposition manner. In some specific implementations, the mass ratio of the porous carbon material to the nano silicon is preferably 1:0.67~1.22. Within this ratio range, the metal oxide can be guaranteed to enter the porous carbon material pores. In some specific implementations, the metal oxide includes but is not limited to TiO2, Al2O3, ZrO2, SnO2, ZnO, Fe2O3 and Co3O4, which can be one or more of them. When it is two or more of them, the application does not have any special restrictions on the amount ratio of each specific substance. In some specific implementations, the metal oxide is preferably TiO2 or Al2O3.

[0048] The surface of the porous carbon material is loaded with metal oxides and graphene. In some specific implementations, the metal oxides include but are not limited to TiO2, Al2O3, ZrO2, SnO2, ZnO, Fe2O3 and Co3O4, and can be one or more of them. When it is two or more of them, the present application has no special restrictions on the usage ratio of each specific substance. In some specific implementations, the metal oxide is preferably TiO2 or Al2O3. In some specific implementations, the graphene can be a graphene sheet prepared by mechanical exfoliation or oxidation-reduction, for example, it can include 2 to 10 layers, preferably 2 to 8 layers, and the size of the layer is 1μm~15μm, preferably 2μm~13μm.

[0049] In fact, in the nano-silicon-carbon negative electrode material provided by the present application, nano-silicon is deposited in the pores of the porous carbon material, metal oxides are dispersed in the pores and on the surface of the porous carbon material, and graphene is coated on the surface of the porous carbon material, which greatly optimizes the performance of the silicon-carbon negative electrode material and makes it have the physical characteristics of low expansion and high cycle rate.

[0050] In some specific implementations, the nano silicon carbon negative electrode material includes:

[0051] 40wt%~55wt% porous carbon material;

[0052] 40wt%~55wt% nano silicon;

[0053] 0.5wt%~5wt% of metal oxide;

[0054] 0.3wt%~5wt% graphene.

[0055] In some specific implementations, the nano silicon carbon negative electrode material includes:

[0056] 45wt%~50wt% porous carbon material;

[0057] 45wt%~50wt% nano silicon;

[0058] 1wt%~3wt% of metal oxide;

[0059] 0.5wt%~3wt% graphene.

[0060] In order to avoid oxidation of nano-silicon, in some specific implementations, the nano-silicon-carbon negative electrode material further includes a passivation layer coated on the surface of the nano-silicon. In some specific implementations, the passivation layer is amorphous carbon or silicon oxide SiO x .

[0061] The present application also provides a method for preparing the nano silicon-carbon negative electrode material described in the above technical solution, comprising the following steps:

[0062] a) depositing nano-silicon on a porous carbon material as a substrate, so that the nano-silicon is deposited in the pores of the porous carbon material to obtain a porous carbon material loaded with nano-silicon;

[0063] b) Modifying the porous carbon material loaded with nano-silicon by using metal oxide and graphene, so that the metal oxide is loaded in the pores and on the surface of the porous carbon material, and the graphene is loaded on the surface of the porous carbon material, to obtain a nano-silicon-carbon negative electrode material.

[0064] The present application first uses a porous carbon material as a substrate to deposit nano-silicon, so that nano-silicon is deposited in the pores of the porous carbon material to obtain a porous carbon material loaded with nano-silicon. When depositing nano-silicon, the amount of silicon deposition is controlled so that it does not completely occupy the pores of the porous carbon material. Specifically, the present application uses a porous carbon material as a substrate and silane as a silicon source for chemical vapor deposition, so that the mass ratio of the porous carbon material and the amount of silicon deposition is 1:0.67~1.22, and a porous carbon material that loads nano-silicon and does not completely occupy the pore space is obtained. In some specific implementations, the equipment for the chemical vapor deposition can be selected from a vacuum furnace, a fluidized bed, a horizontal rotary furnace, etc., and the present application has no special restrictions on this. In some specific implementations, the silane includes but is not limited to monosilane, trisilane, dichlorosilane, trichlorosilane, and tetrachlorosilane, which can be one or more of them. When it is two or more of them, the present application does not limit the proportion of each specific substance.

[0065] The present application first adds the porous carbon material to the chemical vapor deposition equipment, and introduces silane for deposition after heating. In some specific implementations, the heating rate is 1°C / min~10°C / min, preferably 3°C / min~8°C / min, preferably heated to 400°C~600°C, and more preferably heated to 450°C~550°C. In some specific implementations, the silane flow rate is 1L / min~5L / min, preferably 1.5L / min~4.5L / min, and the introduction time is 200min~300min, preferably 220min~260min.

[0066] After the deposition forms nano-silicon, it is preferred to further include a step of forming a passivation layer on the surface of the nano-silicon to protect the nano-silicon particles. In some specific implementations, the passivation layer can be amorphous carbon or silicon oxide SiO x .

[0067] Specifically, when the passivation layer is amorphous carbon, it can be formed by deposition, including the following steps:

[0068] A porous carbon material loaded with nano-silicon is used as a substrate, and a carbon source is introduced for vapor phase chemical deposition, wherein the carbon source includes but is not limited to gases such as acetylene and methane.

[0069] In the present application, after a silicon layer is deposited on a porous carbon material, a carbon source is introduced after the temperature is continuously raised to deposit amorphous carbon. In some specific implementations, the heating rate is 1°C / min~10°C / min, preferably 3°C / min~8°C / min, preferably heated to 500°C~700°C, and more preferably heated to 550°C~650°C. In some specific implementations, the carbon source has an inlet flow rate of 1L / min~5L / min, preferably 1.2L / min~3L / min, more preferably 1.2 L / min~1.5 L / min, and the inlet time is 20min~200min, preferably 60min~190min.

[0070] A typical preparation method for depositing silicon and amorphous carbon is as follows:

[0071] 1 kg of porous carbon was added to the CVD deposition equipment, and the temperature was raised to 500°C at 5°C / min, and 3 L / min of monosilane was introduced for 220 min, and the theoretical silicon deposition amount was 825 g. Then, the temperature of the reactor was raised to 600°C, and 1.5 L / min of acetylene was introduced for 40 min to coat the amorphous carbon to avoid oxidation of the nano-silicon particles, and a porous carbon material loaded with nano-silicon was obtained.

[0072] When the passivation layer is silicon oxide, it can be formed by surface oxidation, which specifically includes the following steps:

[0073] A mixed gas of oxygen and nitrogen is introduced to oxidize the surface of the nano-silicon particles to form silicon oxide.

[0074] In some specific implementations, the volume content of oxygen in the mixed gas is preferably 1% to 5%, preferably 2% to 4%.

[0075] In the present application, a silicon layer is deposited on a porous carbon material, and after cooling, a mixed gas of oxygen and nitrogen is introduced to form silicon oxide. In some specific implementations, the temperature is lowered to 50°C to 200°C, preferably to 80°C to 150°C. In some specific implementations, the flow rate of the mixed gas of oxygen and nitrogen is 0.1L / min to 0.5L / min, preferably 0.2L / min to 0.4L / min, and the introduction time is 100min to 500min, preferably 200min to 400min.

[0076] A typical method for depositing silicon and silicon oxide is as follows:

[0077] 1 kg of porous carbon was added into the CVD deposition equipment, and the temperature was raised to 520°C at 5°C / min. 3 L / min of monosilane was introduced for 260 min. When the temperature of the furnace dropped to 100°C, a nitrogen and oxygen mixture containing a trace amount of oxygen (3%) was introduced for silicon oxide coating at a flow rate of 0.3 L / min. The mixture was ventilated for 300 min to obtain a porous carbon material loaded with nano-silicon.

[0078] After obtaining the porous carbon material loaded with nano-silicon, the porous carbon material loaded with nano-silicon is modified by using metal oxide and graphene, so that the metal oxide is loaded in the pores and on the surface of the porous carbon material, and the graphene is loaded on the surface of the porous carbon material, so as to obtain the nano-silicon carbon negative electrode material.

[0079] The present application has no particular limitation on the modification method, and metal oxide and graphene can be modified simultaneously, for example:

[0080] The porous carbon material loaded with nano-silicon is dispersed and mixed with a metal oxide precursor and a graphene dispersion, and then subjected to heat treatment to obtain a nano-silicon-carbon negative electrode material;

[0081] It is also possible to first use metal oxides for modification and then use graphene for modification, for example:

[0082] The porous carbon material loaded with nano-silicon is dispersed, mixed with a metal oxide precursor, heat-treated, mixed with a graphene dispersion, and spray-dried to obtain a nano-silicon-carbon negative electrode material.

[0083] It is also possible to first use graphene for modification and then use metal oxide for modification, for example:

[0084] The porous carbon material loaded with nano-silicon is dispersed, mixed with a graphene dispersion, spray-dried, and then mixed with a metal oxide precursor and heat-treated to obtain a nano-silicon-carbon negative electrode material.

[0085] Specifically, the present application adopts a solid phase precipitation method to make the metal oxide precursor form metal oxide in the pores and on the surface of the porous carbon material. The present application has no special restrictions on the metal oxide precursor, which can be a salt, hydroxide, metal acid salt, etc. of the metal oxide mentioned above, for example, tetrabutyl titanate, tetraisopropyl titanate, aluminum chloride, etc.

[0086] When metal oxide and graphene are modified simultaneously, the present application first disperses the porous carbon material loaded with nano-silicon in a solvent, for example, in ethanol, then adds the metal oxide precursor to disperse evenly, and finally adds the graphene dispersion, mixes evenly, and filters and dries; the dried powder is heat-treated to obtain a nano-silicon carbon negative electrode material. In some specific implementations, after adding the graphene dispersion, the mixture is mixed evenly and reacted under stirring, and the reaction time is preferably 3h~8h, more preferably 4h~6h. In some specific implementations, the filtering method is suction filtration, and the drying method is drying. In some specific implementations, the heat treatment is performed in a tubular furnace, preferably under the protection of an inert atmosphere. In some specific implementations, the temperature of the heat treatment is preferably 300℃~600℃, more preferably 400~500℃, and the time is 1h~5h, preferably 2h~4h.

[0087] When the modification is first performed with metal oxide and then with graphene, the present application first disperses the porous carbon material loaded with nano-silicon in a solvent, for example, in ethanol, and then adds the metal oxide precursor to disperse evenly, and heat-treats after drying to obtain a porous carbon material loaded with metal oxide. In some specific implementations, the drying is specifically to disperse the metal oxide precursor evenly, evaporate the solvent at 60°C to 80°C, and then treat it in a constant temperature and humidity chamber at 30°C to 50°C for 10h to 15h. In some specific implementations, the heat treatment is performed in a tube furnace, preferably under the protection of an inert atmosphere. In some specific implementations, the temperature of the heat treatment is preferably 300°C to 600°C, more preferably 400 to 500°C, and the time is 1h to 5h, preferably 2h to 4h. Then, after the obtained powder is evenly mixed with the graphene dispersion, it is spray-dried to coat the graphene on the surface of the porous carbon material. The present application has no special restrictions on the parameters of the spray drying, and the parameters and methods commonly used by those skilled in the art can be used. In some specific implementations, the spray drying temperature is 200° C. to 250° C., the rotation speed of the atomizer is 20000 r / min to 25000 r / min, and the drying speed is 5 L / h to 15 L / h.

[0088] When graphene is first used for modification and then metal oxide is used for modification, the present application first disperses the porous carbon material loaded with nano-silicon in a solvent, for example, in ethanol, then adds the graphene dispersion and mixes evenly, and then sprays and dries to coat the graphene on the surface of the porous carbon material. The present application has no special restrictions on the parameters of the spray drying, and the parameters and methods commonly used by those skilled in the art can be used. In some specific implementations, the temperature of the spray drying is 200°C~250°C, the speed of the atomizer is 20000r / min~25000r / min, and the drying speed is 5L / h~15 L / h. After obtaining the porous carbon material coated with graphene, it is evenly dispersed with the metal oxide precursor, dried and heat treated to obtain a porous carbon material loaded with metal oxide. In some specific implementations, the drying is specifically to disperse the metal oxide precursor evenly, evaporate the solvent at 60°C~80°C, and then treat it in a constant temperature and humidity chamber at 30°C~50°C for 10h~15h. In some specific implementations, the heat treatment is carried out in a tube furnace, preferably under the protection of an inert atmosphere. In some specific implementations, the heat treatment temperature is preferably 300°C to 600°C, more preferably 400 to 500°C, and the time is 1h to 5h, preferably 2h to 4h. A typical metal oxide TiO2 synergistic graphene modification process is as follows:

[0089] The porous carbon material after nano-silicon deposition was dispersed in an ethanol solution, a certain amount of tetrabutyl titanate was added and stirred and dispersed, and then a graphene oxide dispersion with a solid content of 0.5% was added, stirred and reacted for 5 hours, and then filtered and dried. The obtained material was placed in a tube furnace and annealed at 450°C for 3 hours under inert atmosphere protection to obtain a nano-silicon-carbon negative electrode material modified by TiO2 and graphene.

[0090] See also Figure 1 , Figure 1 A schematic flow chart of the preparation method provided in an embodiment of the present application, firstly, nano-silicon is deposited on a porous carbon material as a substrate, wherein the nano-silicon is deposited in the pores of the porous carbon material but does not completely fill the pores; then, metal oxides such as carbon dioxide and graphene are modified, wherein the metal oxides simultaneously enter the pores of the porous carbon material to fill the pores and form a coating on the surface of the porous carbon material, while the graphene material forms a coating on the surface of the porous carbon material.

[0091] The present application also provides an electrode plate, comprising the nano silicon-carbon negative electrode material described in the above technical solution or the nano silicon-carbon negative electrode material prepared according to the preparation method described in the above technical solution.

[0092] In some specific implementations, the electrode plate includes a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, and the negative electrode active material layer includes the nano silicon carbon negative electrode material described in the above technical solution or the nano silicon carbon negative electrode material prepared according to the preparation method described in the above technical solution. In some specific implementations, the negative electrode current collector can be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the negative electrode current collector can be aluminum foil. A negative electrode active material layer is provided on the surface of the negative electrode current collector, which includes a negative electrode material, an optional conductive agent, an optional binder and an optional thickener. In some specific implementations, the mass ratio of the negative electrode material, the conductive agent, the binder and the thickener is 80~90:5~15:0~5, preferably 82~87:7~12:0.5~3. In some specific implementations, the negative electrode material includes but is not limited to graphite, hard carbon, soft carbon, lithium titanate, silicon-based composite materials, tin-based composite materials, and can be one or more of them. When the negative electrode material is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. In some specific implementations, the conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, silver powder, nickel powder, tin oxide, conductive titanium dioxide, etc., which can be one or more of them. When the conductive agent is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between each specific substance. The binder includes but is not limited to styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), etc., which can be one or more of them. When the binder is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between each specific substance. The thickener includes but is not limited to sodium hydroxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), etc., and can be one or more of them. When the thickener is a mixture of multiple specific substances, the present application does not impose too many restrictions on the ratio between the specific substances.

[0093] The present application has no special restrictions on the preparation method of the electrode sheet. The nano silicon-carbon negative electrode material described in the above technical solution or the nano silicon-carbon negative electrode material prepared by the preparation method described in the above technical solution, an optional conductive agent, an optional binder and an optional thickener are mixed evenly in a solvent, such as deionized water, and coated on the negative electrode current collector in an optional manner, and the negative electrode sheet can be obtained after drying. Furthermore, after drying, rolling, punching, etc. are also included, and the present application has no special restrictions on them.

[0094] The present application also provides a battery cell, comprising the electrode plate described in the above technical solution.

[0095] Specifically, the battery cell includes a positive electrode sheet, the electrode sheet described in the above technical solution as a negative electrode sheet, a separator separating the positive electrode sheet and the negative electrode sheet, and an electrolyte.

[0096] The negative electrode plate is as described above, and will not be described in detail in this application.

[0097] The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. In some specific implementations, the positive electrode current collector can be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the positive electrode current collector can be aluminum foil. A positive electrode active material layer is provided on the surface of the positive electrode current collector, which includes a positive electrode material, an optional conductive agent and an optional binder. In some specific implementations, the mass ratio of the positive electrode material, the conductive agent and the binder is 90~98:1~5:1~5, preferably 92~95:2~4:1.5~2. In some specific implementations, the positive electrode material includes but is not limited to LiFePO4, LiCoO2, LiNi x Co y Mn 1-x-y O2、LiMn2O 4、 Na (Ni 0.5 Mn 0.5 ) x Fe 1-x O2, Na3V2(PO4)3, Na2FeFe (CN)6, etc., can be one or more of them. When the positive electrode material is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. In some specific implementations, the conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, silver powder, nickel powder, tin oxide, conductive titanium dioxide, etc., can be one or more of them. When the conductive agent is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between each specific substance. The binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyamide, lithium polyacrylate, methacrylate, sodium polymethylcellulose, aluminum dihydrogen phosphate, etc., can be one or more of them. When the binder is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between each specific substance.

[0098] The present application has no special restrictions on the preparation method of the positive electrode sheet. The positive electrode material, the optional conductive agent and the optional binder are uniformly mixed in a solvent, such as N-methylpyrrolidone (NMP), coated on the positive electrode current collector in an optional manner, and dried to obtain the positive electrode sheet. Furthermore, after drying, rolling, slicing, etc. are also included, and the present application has no special restrictions on them.

[0099] In some specific implementations, the diaphragm includes but is not limited to glass fiber microporous membrane, polyester microporous membrane, polyethylene microporous membrane, polypropylene microporous membrane, polytetrafluoroethylene microporous, ceramic coated diaphragm, etc.

[0100] In some specific implementations, the electrolyte may include a lithium salt, an organic solvent, and an additive, wherein the lithium salt includes but is not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2 ), one or more of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP), preferably lithium hexafluorophosphate; the organic solvent includes but is not limited to ethylene carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, ethyl propionate, ethyl acetate, methyl acetate, dimethyl acetate, methyl butyrate, and n-propyl acetate, preferably a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC), wherein the volume ratio of EC to DEC is 1~2:1~2, more preferably 1:1; the additive includes but is not limited to one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, diphenyl carbonate, toluene carbonate, acrylic nitrile, succinic anhydride, succinonitrile, and adiponitrile.

[0101] In some specific implementations, in the electrolyte, the electrolyte is lithium hexafluorophosphate, the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC), the volume ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is preferably 1~2:1~2, more preferably 1:1, and the concentration of the electrolyte is 0.5 mol / L~2 mol / L, preferably 0.8 mol / L ~1.5 mol / L.

[0102] In the present application, a positive electrode sheet, a separator and a negative electrode sheet are stacked in sequence to obtain a battery cell assembly, which is sealed in an aluminum-plastic bag, and an electrolyte is injected. After packaging, standing, forming and other processes, a battery cell is obtained.

[0103] The present application provides a nano silicon carbon negative electrode material, including a porous carbon material, nano silicon and metal oxides loaded in the pores of the porous carbon material, and metal oxides and graphene loaded on the surface of the porous carbon material. The present application uses metal oxides and graphene to modify the porous carbon material loaded with nano silicon, making full use of the low expansion rate and high mechanical stability of metal oxides, and the high electrical conductivity, high mechanical strength, and high thermal conductivity of graphene. While coating the porous carbon material, the metal oxide enters the pores of the porous material to reduce the first expansion rate of the nano silicon carbon negative electrode material and improve its cycle performance. The experimental results show that compared with the modification using metal oxide alone, its first expansion rate decreases by 5%, and the 100-cycle cycle performance increases by 26%; compared with the modification using graphene alone, its first expansion rate decreases by 3%, and the 100-cycle cycle performance increases by 11%.

[0104] The nano silicon-carbon negative electrode material, its preparation method and its application provided by the present application are further described below in conjunction with the embodiments.

[0105] Example 1

[0106] Phenolic resin-based porous carbon (BET: 1750m 2 / g; micropores account for 40%; pore volume 0.75cc / g, average pore size 2nm) 1kg, added to a fluidized bed CVD device, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was 260min; the temperature in the furnace was raised to 650℃, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5L / min, and the ventilation was 150min, and a porous carbon loaded with nano-silicon in which amorphous carbon was coated on the surface of nano-silicon particles was obtained, and the obtained porous carbon loaded with nano-silicon was incompletely filled;

[0107] Take 10g of the above-mentioned porous carbon loaded with nano-silicon and disperse it in an ethanol solution, add 2g of tetrabutyl titanate (AR grade) and stir and disperse it; add 18g of graphene oxide dispersion with a solid content of 0.5% dropwise, stir and react for 5 hours, then filter and dry; place the obtained material in a tubular furnace, anneal at 500°C for 3h under the protection of a high-purity nitrogen atmosphere, and obtain a TiO2 / graphene synergistically modified nano-silicon-carbon negative electrode material.

[0108] See also Figure 2 , Figure 2 The SEM image of the TiO2 / graphene synergistically modified nano-silicon-carbon negative electrode material prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the porous carbon surface is loaded with TiO2 and graphene.

[0109] The nano silicon carbon negative electrode material is assembled into a CR2032 button battery, and the preparation method is as follows: slurry is homogenized according to the following ratio: nano silicon carbon negative electrode material (84%), single wall carbon nanotubes (SWCNTs, 1%), carbon black SP (10%), binder PAA (5%), and the obtained slurry is coated on 8μm copper foil with a coating thickness of 80μm. The negative electrode slurry is dried after being scraped, rolled and punched. The prepared negative electrode sheet is used as the positive electrode, the metal lithium sheet is used as the negative electrode, PP / PE is used as the separator, and LiPF6 / EC+DEC+DMC (the volume ratio of EC, DEC and DMC is 1:1:1) is used as the electrolyte, and assembled in an argon-filled glove box.

[0110] The upper limit of the charging voltage is 2V, the lower limit of the discharge is 0.005V, the first cycle charge and discharge rate is 0.1C, and the cycle rate is 0.2C. Its performance is shown in Table 1 and Figure 3 As shown in Table 1, the performance test results provided by the embodiments and comparative examples of the present application are as follows: Figure 3 This is the first cycle charge and discharge curve of the TiO2 / graphene synergistically modified nano silicon carbon negative electrode material prepared in Example 1.

[0111] Example 2

[0112] Phenolic resin-based porous carbon (BET: 1750m 2 / g; micropores account for 40%; pore volume 0.75cc / g, average pore size 2nm) 1kg, added to a fluidized bed CVD device, the temperature was raised to 520℃ and trisilane was introduced, the trisilane flow rate was 1.5L / min, and the ventilation was 420min; the temperature in the furnace was raised to 650℃, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.2L / min, and the ventilation was 190min to obtain amorphous carbon coated on the surface of nano-silicon particles. The porous carbon loaded with nano-silicon is incompletely filled;

[0113] Take 10g of the above-mentioned porous carbon loaded with nano-silicon and disperse it in an ethanol solution, add 2g of tetrabutyl titanate (AR grade) and stir and disperse it; add 18g of graphene oxide dispersion with a solid content of 0.5% dropwise, stir and react for 5 hours, then filter and dry; place the obtained material in a tubular furnace, anneal at 500°C for 3h under the protection of a high-purity nitrogen atmosphere, and obtain a TiO2 / graphene synergistically modified nano-silicon-carbon negative electrode material.

[0114] The battery was assembled into a CR2032 button cell according to the method of Example 1 and tested. The performance of the battery is shown in Table 1.

[0115] Example 3

[0116] Select biomass porous carbon (BET: 1800m 2 / g; micropore proportion 55%; pore volume 0.8cc / g, average pore size 2.5nm) 1kg, added to the fluidized bed CVD equipment, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was carried out for 220min; the temperature in the furnace was raised to 650℃, acetylene was introduced, the flow rate was set to 1.5L / min, and the ventilation was carried out for 60min to obtain amorphous carbon coated on the surface of nano-silicon particles. The porous carbon loaded with nano-silicon is incompletely filled;

[0117] Take 10g of the above-mentioned porous carbon loaded with nano-silicon and disperse it in an ethanol solution, add 3g of tetrabutyl titanate (AR grade) and stir and disperse; slowly add 5.5g of graphene dispersion with a solid content of 2%, stir and react for 5h, then filter and dry; place the obtained material in a tubular furnace, anneal at 500℃ for 3h under the protection of high-purity nitrogen atmosphere to obtain TiO2 / graphene synergistically coated nano-silicon-carbon negative electrode material.

[0118] The battery was assembled into a CR2032 button cell according to the method of Example 1, and its performance is shown in Table 1.

[0119] Example 4

[0120] Select biomass porous carbon (BET: 1800m 2 / g; micropores account for 70%; pore volume 0.8cc / g, average pore size 2.5nm) 1kg, added to the fluidized bed CVD equipment, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was carried out for 260min; the temperature in the furnace was raised to 650℃, methane was introduced, the flow rate was set to 1.5L / min, and the ventilation was carried out for 60min to obtain amorphous carbon coated on the surface of nano-silicon particles. The porous carbon loaded with nano-silicon is incompletely filled;

[0121] Take 10g of the above-mentioned porous carbon loaded with nano-silicon and disperse it in an ethanol solution, add 2.8g of tetraisopropyl titanate, stir and disperse, and then evaporate the solvent at 70°C. The resulting product is placed in a constant temperature and humidity chamber at 40°C for 12 hours and then placed in a tubular furnace. Annealing is carried out at 500°C for 3 hours under the protection of a high-purity nitrogen atmosphere; the obtained TiO2 coated material and graphene dispersion are blended in a mass ratio of 90:10, and graphene sheets are coated using spray drying to obtain TiO2 / graphene synergistically coated nano-silicon-carbon negative electrode material.

[0122] The battery was assembled into a CR2032 button cell according to the method of Example 1, and its performance is shown in Table 1.

[0123] Example 5

[0124] Phenolic resin-based porous carbon (BET: 1750m 2 / g; micropores account for 40%; pore volume 0.75cc / g, average pore size 2nm) 1kg, added to a fluidized bed CVD device, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was 260min; the temperature in the furnace was raised to 650℃, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5L / min, and the ventilation was 150min, and a porous carbon loaded with nano-silicon in which amorphous carbon was coated on the surface of nano-silicon particles was obtained, and the obtained porous carbon loaded with nano-silicon was incompletely filled;

[0125] Take 1kg of the porous carbon loaded with nano-silicon and disperse it in 15L of aqueous solution. After complete dispersion, add 1L of graphene dispersion with a solid content of 3% (number of layers ≤ 5 layers). After homogeneous dispersion, spray drying is carried out, the drying temperature is 220°C, the atomizer speed is 22000r / min, and the drying speed is 10L / h. Take 10g of the obtained graphene-coated porous carbon material loaded with nano-silicon, disperse it in 250mL of 2% PVP aqueous solution, add 1.5g of aluminum chloride and stir and disperse it, then add ammonia water dropwise to adjust the pH of the solution to 9, stir and react at 70°C for 5h, centrifuge after the reaction is completed, wash and dry, place the obtained material in a tubular furnace, anneal at 600°C for 5h under the protection of high-purity nitrogen atmosphere, and obtain Al2O3 / graphene synergistically modified nano-silicon carbon negative electrode material.

[0126] The battery was assembled into a CR2032 button cell according to the method of Example 1, and its performance is shown in Table 1.

[0127] Example 6

[0128] Phenolic resin-based porous carbon (BET: 1750m 2 / g; micropores account for 40%; pore volume 0.75cc / g, average pore size 2nm) 1kg, added to the fluidized bed CVD equipment, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was 260min; the heating was stopped, and when the furnace temperature dropped to 100℃, an oxygen-nitrogen mixed gas containing a trace amount of oxygen (3%) was introduced to carry out SiO x Coating, set the flow rate to 0.3L / min, ventilation for 300min, get SiO x The nano-silicon-loaded porous carbon is coated on the surface of the nano-silicon particles, and the obtained nano-silicon-loaded porous carbon is incompletely filled;

[0129] Take 1kg of the porous carbon loaded with nano-silicon and disperse it in 15L of aqueous solution. After complete dispersion, add 1.2L of graphene dispersion with a solid content of 3% (number of layers ≤ 5 layers). After homogeneous dispersion, spray drying is carried out, the drying temperature is 220°C, the atomizer speed is 22000r / min, and the drying speed is 10L / h. Take 10g of the obtained graphene-coated porous carbon material loaded with nano-silicon, disperse it in 250mL of 2% PVP aqueous solution, add 1.5g of aluminum chloride and stir and disperse it, then add ammonia water dropwise to adjust the pH of the solution to 9, stir and react at 70°C for 5h, centrifuge after the reaction is completed, wash and dry, place the obtained material in a tubular furnace, anneal at 600°C for 5h under the protection of high-purity nitrogen atmosphere, and obtain Al2O3 / graphene synergistically modified nano-silicon carbon negative electrode material.

[0130] The battery was assembled into a CR2032 button cell according to the method of Example 1, and its performance is shown in Table 1.

[0131] Comparative Example 1

[0132] Phenolic resin-based porous carbon (BET: 1750m 2 / g; micropores account for 40%; pore volume 0.75cc / g, average pore size 2nm) 1kg, added to the fluidized bed CVD equipment, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was 280min; the temperature in the furnace was raised to 650℃, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5L / min, and the ventilation was 150min. According to the test method described in patent PCT / US2021 / 052995, the floating silicon content of the obtained nano-silicon-carbon negative electrode material was 3%, indicating that there were basically no pores on its surface that could be filled with oxides.

[0133] Take 10g of the porous carbon loaded with nano-silicon and disperse it in an ethanol solution, add 2g of tetrabutyl titanate (AR grade) and stir and disperse it, add 18g of graphene oxide dispersion with a solid content of 0.5% dropwise, stir and react for 5h, then filter and dry, place the obtained material in a tube furnace, anneal at 500℃ for 3h under the protection of high-purity nitrogen atmosphere, and obtain TiO2 / graphene-coated nano-silicon carbon negative electrode material. Because the surface silicon has completely blocked the surface pores, TiO2 cannot fill into the porous carbon.

[0134] The battery was assembled into a CR2032 button cell according to the method of Example 1, and its performance is shown in Table 1.

[0135] Comparative Example 2

[0136] Phenolic resin-based porous carbon (BET: 1850m 2 / g; micropores account for 70%; pore volume 0.85cc / g, average pore size 2nm) 1kg, added to the fluidized bed CVD equipment, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was 260min; the temperature in the furnace was raised to 650℃, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5L / min, and the ventilation was 150min. The porous carbon loaded with nano-silicon was incompletely filled;

[0137] Take 10g of the above-mentioned porous carbon loaded with nano-silicon and disperse it in an ethanol solution, add 2g of tetrabutyl titanate (AR grade) and stir and disperse it, add 10g of deionized water dropwise, stir and react for 5h, then filter and dry, place the obtained material in a tubular furnace, anneal at 500℃ for 3h under the protection of high-purity nitrogen atmosphere, and obtain TiO2-coated nano-silicon-carbon negative electrode material.

[0138] The battery was assembled into a CR2032 button cell according to the method of Example 1, and its performance is shown in Table 1.

[0139] Comparative Example 3

[0140] Phenolic resin-based porous carbon (BET: 1750m 2 / g; micropores account for 40%; pore volume 0.75cc / g, average pore size 2nm) 1kg, added to the fluidized bed CVD equipment, the temperature was raised to 520℃ and monosilane was introduced, the monosilane flow rate was 3L / min, and the ventilation was 260min; the temperature in the furnace was raised to 650℃, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5L / min, and the ventilation was 150min. The porous carbon loaded with nano-silicon was incompletely filled;

[0141] Take 1kg of the porous carbon loaded with nano-silicon and disperse it in 15L of aqueous solution. After it is completely dispersed, add 1.5L of graphene dispersion with a solid content of 3% (number of layers ≤ 5 layers). After homogeneous dispersion, spray drying is performed at a drying temperature of 220°C, an atomizer speed of 22000r / min, and a drying speed of 10L / h. A graphene-modified nano-silicon-carbon negative electrode material is obtained.

[0142] Table 1 Performance test results provided by the examples and comparative examples of the present application

[0143]

[0144] As can be seen from Table 1, the metal oxide / graphene synergistically modified nano silicon-carbon negative electrode material provided in the present application has a lower first-cycle lithium insertion expansion rate and a higher capacity retention rate.

[0145] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A nano silicon-carbon negative electrode material, comprising: Porous carbon materials; Nano-silicon and metal oxides loaded in the pores of the porous carbon material; Metal oxide and graphene are loaded on the surface of the porous carbon material.

2. The nano silicon-carbon negative electrode material according to claim 1, characterized in that: include: 40wt%~55wt% porous carbon material; 40wt%~55wt% nano silicon; 0.5wt%~5wt% of metal oxide; 0.3wt%~5wt% graphene.

3. The nano silicon-carbon negative electrode material according to claim 1, characterized in that: The specific surface area of ​​the porous carbon material is 1300 m 2 / g ~2200m 2 / g; micropores account for 40%~90%; average pore size is 1.8nm~4nm; pore volume is 0.6 cc / g ~1.1cc / g.

4. The nano silicon-carbon negative electrode material according to claim 1, characterized in that: The metal oxide is selected from at least one of TiO2, Al2O3, ZrO2, SnO2, ZnO, Fe2O3 and Co3O4.

5. The nano silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: It also includes a passivation layer coated on the surface of the nano-silicon; The passivation layer is amorphous carbon or silicon oxide.

6. The method for preparing the nano silicon carbon negative electrode material according to any one of claims 1 to 4, comprising the following steps: a) depositing nano-silicon on a porous carbon material as a substrate, so that the nano-silicon is deposited in the pores of the porous carbon material to obtain a porous carbon material loaded with nano-silicon; b) Modifying the porous carbon material loaded with nano-silicon by using metal oxide and graphene, so that the metal oxide is loaded in the pores and on the surface of the porous carbon material, and the graphene is loaded on the surface of the porous carbon material, to obtain a nano-silicon-carbon negative electrode material.

7. The preparation method according to claim 6, characterized in that: Step a) specifically includes: Chemical vapor deposition is carried out using a porous carbon material as a substrate and silane as a silicon source, so that the mass ratio of the porous carbon material to the silicon deposition amount is 1:0.67-1.22, thereby obtaining a porous carbon material loaded with nano-silicon.

8. The preparation method according to claim 7, characterized in that: Step b) specifically includes: The porous carbon material loaded with nano-silicon is dispersed and mixed with a metal oxide precursor and a graphene dispersion, and then subjected to heat treatment to obtain a nano-silicon-carbon negative electrode material; Alternatively, step b) specifically comprises: The porous carbon material loaded with nano-silicon is dispersed, mixed with a metal oxide precursor, heat treated, mixed with a graphene dispersion, and spray-dried to obtain a nano-silicon-carbon negative electrode material; Alternatively, step b) specifically comprises: The porous carbon material loaded with nano-silicon is dispersed, mixed with a graphene dispersion, spray-dried, and then mixed with a metal oxide precursor and heat-treated to obtain a nano-silicon-carbon negative electrode material.

9. The preparation method according to claim 6, characterized in that: Before step b), the method further comprises: Deposition of a passivation layer is performed using a porous carbon material loaded with nano-silicon as a substrate; The passivation layer is amorphous carbon or silicon oxide.

10. An electrode plate, comprising the nano silicon-carbon negative electrode material according to any one of claims 1 to 5 or the nano silicon-carbon negative electrode material prepared according to the preparation method according to claims 6 to 9.

Citation Information

Patent Citations

  • Device and method for filtering a fluid circulating in a plumbing and heating system

    US20210052995A1

Cited By

  • Silicon-carbon negative electrode material applied to sulfide solid-state battery and modification method of silicon-carbon negative electrode material

    CN120237195A

  • Spherical multilayer carbon-based material as well as negative electrode and preparation method thereof

    CN120933331A